2017
DOI: 10.1101/184788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snord116-dependent diurnal rhythm of DNA methylation in mouse cortex

Abstract: Rhythmic oscillations of physiological processes depend on integrating the circadian clock and diurnal environment. DNA methylation is epigenetically responsive to daily rhythms, as a subset of CpG dinucleotides in brain exhibit diurnal rhythmic methylation. A major genetic effect on rhythmic methylation was identified in a mouse Snord116 deletion model of the imprinted disorder Prader-Willi syndrome (PWS). Of the >23,000 diurnally rhythmic CpGs identified in wild-type cortex, 97% lost rhythmic methylation in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…The complementary co‐expression network analysis further revealed a module of 224 co‐expressed genes in maternal blood showing an association with folic acid and 5‐MeTHF levels in the opposite direction from ASD risk that could not be explained by cell type differences. Interestingly, these ASD and nutrient associated genes were functionally enriched for DNA methylation binding and methylation‐dependent chromatin silencing, consistent with prior DNA methylation changes observed in ASD [Coulson et al, 2018; Mordaunt et al, 2020; Vogel Ciernia et al, 2019; Zhu et al, 2019] as well as ASD‐like syndromes associated with methyl binding proteins [Cukier et al, 2012; Cukier et al, 2010]. MBD3L , which has methyl‐binding function, is predicted to assist with demethylation reactions and functions as a transcriptional repressor [Fouse, Nagarajan, & Costello, 2010; Mungall, 2002; Zhou et al, 2019].…”
Section: Discussionsupporting
confidence: 83%
“…The complementary co‐expression network analysis further revealed a module of 224 co‐expressed genes in maternal blood showing an association with folic acid and 5‐MeTHF levels in the opposite direction from ASD risk that could not be explained by cell type differences. Interestingly, these ASD and nutrient associated genes were functionally enriched for DNA methylation binding and methylation‐dependent chromatin silencing, consistent with prior DNA methylation changes observed in ASD [Coulson et al, 2018; Mordaunt et al, 2020; Vogel Ciernia et al, 2019; Zhu et al, 2019] as well as ASD‐like syndromes associated with methyl binding proteins [Cukier et al, 2012; Cukier et al, 2010]. MBD3L , which has methyl‐binding function, is predicted to assist with demethylation reactions and functions as a transcriptional repressor [Fouse, Nagarajan, & Costello, 2010; Mungall, 2002; Zhou et al, 2019].…”
Section: Discussionsupporting
confidence: 83%
“…Earlier research using the same Snord116 +/− mutation mice reported disrupted circadian rhythms, sleep-wake cycles, frontal cortical transcriptional and epigenetic regulation, as well as reduced forebrain neuronal and cerebellar cellular sizes, which could mechanistically contribute to the behavioral phenotypes reported (Burnett et al, 2017; Coulson et al, 2018; Lassi, Priano, et al, 2016). Other in vivo model systems of PWS deleted the entire critical imprinting center and reported low locomotor abilities and impairments in the frontal cortical dependent five choice serial reaction time task (Relkovic et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Powell et al 75 identified dysregulation of about 6000 diurnally regulated genes in the mouse cortex, including dysregulation of the pacemaker genes such as Cry1, Clock, Per2 and Mtor as well as increased expression of Ube3a, which regulates the oscillatory pattern of Bmal1 via ubiquitination. 71 Coulson et al 76 further showed that loss of expression for Snord116 led to a pattern of shifted diurnal methylation characterized by losses during the light phase and increased diurnal methylation during the dark phase. The authors suggest that the gene expression of epigenetic and circadian regulators is increased in the model mice during the light phase, which may lead to prolonged accumulation of these proteins into the dark phase, resulting in the shifted methylation pattern.…”
Section: Genetic Bases Of Sleep Phenotypes and Circadian Rhythms In Pws And Asmentioning
confidence: 99%